2019
DOI: 10.1039/c9ja00186g
|View full text |Cite
|
Sign up to set email alerts
|

Performance of sp-ICP-TOFMS with signal distributions fitted to a compound Poisson model

Abstract: Characterization of dissolved background signals as compound Poisson distributed enables more accurate and robust nanoparticle detection thresholds in single-particle ICP-TOFMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 41 publications
0
46
0
Order By: Relevance
“…In our Matlab script, microdroplet signals were isolated from data traces by their multi-element fingerprints, and NPs were identified based on a critical value detection criterion (S C ) that gives a false-positive rate of 0.01%; critical values were based on modelling TOFMS signals as a compound Poisson signal distribution. 32,34 Prior to data analysis in Matlab, TOF spectra were mass calibrated in TOFWARE (ver. 2.5.11, TOFWERK, run in Igor-Pro 7 environment) and exported as .CSV time traces of counts vs. time for all analyte isotopes.…”
Section: Data Analysis: Online Microdroplet Calibration and Sample Upmentioning
confidence: 99%
See 1 more Smart Citation
“…In our Matlab script, microdroplet signals were isolated from data traces by their multi-element fingerprints, and NPs were identified based on a critical value detection criterion (S C ) that gives a false-positive rate of 0.01%; critical values were based on modelling TOFMS signals as a compound Poisson signal distribution. 32,34 Prior to data analysis in Matlab, TOF spectra were mass calibrated in TOFWARE (ver. 2.5.11, TOFWERK, run in Igor-Pro 7 environment) and exported as .CSV time traces of counts vs. time for all analyte isotopes.…”
Section: Data Analysis: Online Microdroplet Calibration and Sample Upmentioning
confidence: 99%
“…Au, Pt, and Ag) and endogenous particles present in the WWTP effluent sample. All NP signals were found by fitting m/z-specific background signals with a compound Poisson distribution 32,34 and then thresholding ICP-TOFMS data at a critical value (S C ) that predicts 0.01% false-positive particle signals. As seen, the determined d eff,i, and PNC values of the spiked engineered NPs match well with expectation.…”
Section: Multiplexed-np Analysis By Sp-icp-tofmsmentioning
confidence: 99%
“…This setup has been described elsewhere. 33,[35][36][37][38]40,41 In this setup, microdroplets are produced by a microdroplet generator (50 mm diameter Autodrop Pipette, AD-KH-501-L6, MD-E-3000 dispensing system, Microdrop Technologies, GmbH, Germany) and introduced via a falling tube that is lled with a He/ Ar gas mixture to accelerate solvent evaporation so that microdroplets are reduced to dried droplet residues by the end of the falling tube. 26,42 Continuously nebulized samples are introduced via a pneumatic nebulizer and spray chamber, and then mixed with microdroplet-aerosols via a t-piece just in front of the injector base of the ICP torch.…”
Section: Methodsmentioning
confidence: 99%
“…59,72 For ICP-TOFMS, we have shown that ion signals are neither Gaussian nor Poisson distributed; instead, signals follow a compound-Poisson distribution that is the result of Poissondistributed ion arrival and the response function of the electron-multiplier detection system. 40,41 Because distributions of ICP-TOFMS signals have a unique compound-Poisson shape, accurate separation of background signals from particle signals requires a distinct critical value, L C(ADC) , that is calculated via Monte Carlo methods. 40 L C(ADC) is the net-signal critical value, i.e.…”
Section: Accurate Single-particle Ndingmentioning
confidence: 99%
“…A detailed explanation of each of these data processing steps is beyond the scope of this reportin part because many aspects of the analysis strategy are reported elsewhere. 36,[38][39][40][41][42] For aspects of this process that are new to the current study, we provide a more detailed discussion below. In addition, our "NanoFinder" software is provided under an open-source license (http://doi.org/10.5905/ethz-1007-363) and is hosted at https://github.com/ethz-tema/TEMAsingleParticle.…”
Section: Data Processingmentioning
confidence: 99%